COMPARISONS BETWEEN HALF‐DAY AND ALL‐DAY SPRING TURKEY HUNTING IN INDIANA - Steven E. Backs (Wildlife Society Bulletin)
Abstract: Wildlife managers have debated whether “half‐day” versus “all‐day” hunting influences the probability of harvesting an adult or a juvenile wild turkey (Meleagris gallopavo) gobbler. Daily and hourly harvest distributions of adult gobblers were compared between 4 years of half‐day hunting (1996–1999; 23,356 harvest events) and 2 years of all‐day hunting in Indiana (2003 and 2004; 21,061 harvest events). The distributions of the total harvest across the 19‐day season were the same for both half‐day and all‐day seasons. During all‐day seasons, 70% of the total harvest occurred before 1000 hr, 79% by noon, 8% between 1200–1600 hr, with 13% after 1600 hr. Adults made up a slightly greater proportion (>2% points on average; e.g., 75% versus 77%) of the harvest for the all‐day seasons. Our data suggest the influence of all‐day hunting on adult gobbler mortality is relatively minor on a statewide basis with a 1‐bird bag limit and the small differences in the proportion of the harvest that was adults may be related to factors other than extended shooting hours. Differential adult mortality may be of greater management concern under more liberal spring harvest strategies.